Deontic modality and persuasion in advertising discourse - Nadja Paulino Pessoa (2007)
This works aims to analyze the use of deontic modal markers in advertising discourse, taking into account the linguistic expressions, the semantic values and the possible sense effects obtained in the construction of persuasion. Therefore, we have tried to establish relationships between the type of deontic target, the type of deontic source, the ascribed deontic values (obligation â permission â prohibition), the speakerâs position in the ascribing of deontic values, the types of deontic modal markers, as well as markers of mitigation and assertiveness that play a role in the argumentativeness of the advertising discourse. For data analysis, the functionalist perspective has been adopted in an attempt to integrate syntactic, semantic and pragmatic-discursive components. Furthermore, to bear in mind that the clausal structure is organized in layers enables the analysis of modality in different levels of acting, as well as allows for observation of the relationships between other categories as mood, time and aspect. In order to evaluate the manifestation of deontic modality, we have made use of 144 advertising texts that were published in national magazines. This corpus was built from the written language database Literatura de Propaganda (LP) available at the Lexicographic Studies Center of the Linguistics Department of Faculdade de CiÃncias e Letras da UNESP de Araraquara. The data analysis revealed that external obligation is the most ascribed deontic value in this type of discourse. As to the deontic target, the majority of the ascribed values converge on the individual. Furthermore, it has been verified that a non-specification of the deontic source is highly common, once it conveys objectivity to the utterance, thus constituting a means of lesser commitment. Opting for the speakerâs exclusion from the ascribing of the deontic values was the most relevant feature, for speakers frequently establish obligations, permissions and prohibitions among themselves. Therefore, as predicted, the deontic modality helps to achieve the reader-consumerâs persuasion.